Short communication. Seed germination of different populations of wild (n=9) Braáica montana and B. oleracea - Perez Garcia, F.
(Es, En)
ilus., 10 ref.
Keywords: BRAáICA; SEMILLAS; GERMINACION; ACIDO GIBERELICO; ESPAÑA; VARIABILIDAD INTERPOBLACIONAL; VARIABILIDAD INTRAESPECIFICA